The Rotterdam Rules: Do They Solve the Problems arising from Multimodal Transportation? - Kituri, Catherine Wanjala (Department of Commercial Law, 2014)
The Convention on Contracts for the International Carriage of Goods Wholly or Partly by Sea was adopted by the United Nations General Assembly on the 11th of December 2008. Shortly afterwards, a signing ceremony in Rotterdam was authorised and a recommendation was made for the new Convention to be known as the 'Rotterdam Rules.' The signing ceremony took place on the 23rd of September 2009 and the Convention has thus far found wide acceptance with over 19 States having signed it. Given that the Convention requires only 20 ratifications to come into force the number of signatories seems a fair indication that the Convention will come into force and, perhaps, in the near future.